PENGARUH PENGGUNAAN LKS BERBASIS INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Florentina Krida Wijayanti; Arwin Achmad; Rini Rita T. Marpaung (Universitas Lampung, 2015)
This research purposed to know the influence of using worksheet based on Guided Inquiry towards students CSP in junior high school on material of Global Warming. Research design was pretest-posttest of the nonequivalent group. Research sample were class VII.1 and VII.2 with purposive sampling technique. The students CSP data that were obtained from the score of pretest, posttest and N-gain were analyzed by t-test. The CSP qualitative data and the responses were analyzed descriptively. The research result was N-gain=76 17. The observation of students CSP was 83,2%. 81.45% of students gave the positive response to the use of the worksheet based on Guided Inquiry. Then, this worksheet based on Guided Inquiry had significant influence in increasing the students CSP on material of Global Warming.Penelitian ini bertujuan mengetahui pengaruh penggunaan LKS berbasis Inkuiri Terbimbing terhadap KPS siswa SMP pada materi Pemanasan Global. Desain penelitian pretest-posttest kelompok tak ekuivalen. Sampel penelitian kelas VII.1 dan VII.2 dengan pengambilan sampel menggunakan teknik purposive sampling. Data KPS siswa yang diperoleh dari nilai pretest, posttest dan N-gain yang dianalisis menggunakan uji-t. Data kualitatif KPS dan tanggapan dianalisis secara deskriptif. Hasil penelitian N-gain = 76 17. Observasi KPS siswa yaitu 83,2%. 81,45% siswa memberikan tanggapan positif terhadap penggunaan LKS berbasis Inkuiri Terbimbing. Sehingga, LKS berbasis Inkuiri Terbimbing berpengaruh signifikan dalam meningkatkan KPS siswa pada materi Pemanasan Global.Kata kunci: inkuiri terbimbing, keterampilan proses sains (KPS), LKS, pemanasan global